Exploring Potential Factors Affecting Reading Comprehension in EAL Learners: A Preliminary Corpus-Based Analysis - Brooks, Gavin; Clenton, Jon; Fraser, Simon (Languages (Basel), 2025)
This article presents a study examining the vocabulary knowledge of English as an additional language (EAL) learners in two international schools in Japan in relation to the vocabulary profiles of the textbooks they are required to use in the classrooms. The vocabulary knowledge of 139 participants from two international schools was assessed using either the New Vocabulary Levels Test (NVLT) or the Updated Vocabulary Levels Test (UVLT). These results were compared to a 15 million-word corpus compiled from representative subject-specific textbooks to estimate the vocabulary coverage participants are likely to achieve. The findings revealed that EAL learners consistently scored lower than a combined group of their first-language English (FLE) and proficient L2 (PL2) peers, with fewer than 25% of EAL learners mastering the AWL before Grade 12. Furthermore, even the most frequent 5000-word bands provided only 91–93% coverage for subjects like biology and chemistry, leaving many EAL learners struggling to comprehend these texts. This analysis highlights the potential difficulties EAL learners may face in understanding the textbooks that are being used in EAL classrooms, underscoring the need for better vocabulary scaffolding and support for such learners in the international school context.